2011
DOI: 10.1002/pen.22186
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationship studies in amine functionalized multiwall carbon nanotubes filled polypropylene composite fiber

Abstract: Amine functionalized multiwalled carbon nanotubes (a‐MWNT) based polypropylene (PP) composite fibers were prepared in the presence of polypropylene‐g‐maleic anhydride (PP‐g‐MA) by melt‐mixing followed by melt‐spinning with subsequent post‐drawing of the as‐spun fibers of varying draw ratio (DR). In order to enhance the interfacial interaction, a‐MWNT were utilized in combination with PP‐g‐MA during melt‐mixing. Fourier transform infrared spectroscopic analysis revealed the formation of imide bonds between MA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…It is clear that the incorporation of SWCNTs increases T c of the composites in comparison with PP/PP‐ g ‐MA, confirming that SWCNTs enhance the nucleation of PP/PP‐ g ‐MA crystallization , . Tambe et al reported the hetero‐nucleating effect of CNTs and that the higher T c of functionalized CNT/PP/PP‐ g ‐MA was attributed to the uniform dispersion of CNTs . Valentini et al also reported that T c of a SWCNT/PP composite was significantly increased due to the nucleation effect .…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…It is clear that the incorporation of SWCNTs increases T c of the composites in comparison with PP/PP‐ g ‐MA, confirming that SWCNTs enhance the nucleation of PP/PP‐ g ‐MA crystallization , . Tambe et al reported the hetero‐nucleating effect of CNTs and that the higher T c of functionalized CNT/PP/PP‐ g ‐MA was attributed to the uniform dispersion of CNTs . Valentini et al also reported that T c of a SWCNT/PP composite was significantly increased due to the nucleation effect .…”
Section: Resultsmentioning
confidence: 83%
“…27,28 Tambe et al reported the hetero-nucleating effect of CNTs and that the higher T c of functionalized CNT/PP/PP-g-MA was attributed to the uniform dispersion of CNTs. 18 Valentini et al also reported that T c of a SWCNT/PP composite was significantly increased due to the nucleation effect. 29 However, the melting temperature decreased on incorporation of SWCNTs, while the heat of fusion was unchanged.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Earlier reports showed that the addition of clay to CNTs significantly improved the debundling of CNTs, resulting in fine dispersions in polymer matrix . Tambe et al reported that uniform distribution of CNT contributed to the increase in crystallinity of PP.…”
Section: Resultsmentioning
confidence: 99%